Penyuluhan Menstruasi Untuk Menurunkan Kecemasan Menghadapi Menarche Pada Remaja Putri Di SMP Itdokter Tengku Hanafi Sei Buluh Kec. Perbaungan - manik, maria hermita (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Anxiety about menarche is a state of feeling characterized by physical tension, worry and the assumption that something bad will happen during menarche. This service aims to provide counseling and counseling for dealing with menarche for young women, service partners with Doctor Tengku Hanafi Sei Buluh IT Middle School, Perbaungan District. The service method used is by providing education about Menarche and counseling related to anxiety in dealing with menarche. The results of the service showed that 17 people did not experience anxiety, 12 people had mild anxiety and 2 people experienced moderate anxiety.